Histomorphological Evaluation of Teeth After Three Months Follow up of Pulp-Cell Homing Procedure in Teeth with Incomplete Apex Formation in Dogs - Ammar Samir Salim; Ghada Younis Abdulrahman (University of Mosul, College of Dentistry, 2021)
Aims: To evaluate the tissues formed by the pulp stem cell homing technique through the histopathological sections, after a three months follow-up period. Materials and Methods: The study was performed on twelve right second premolars of twelve local breed female dogs, that were randomly selected form different areas of Mosul City. The study was divided into four stages, stage I (Induce infection), stage II (Disinfection), stage III (Treatment), and stage IV (3 months follow-up). In the stage IV the tooth and the surrounding bone segment was sectioned and routinely processed to produce H&Estained tissue sections that were evaluated under the light microscope. The histological examiners were evaluated presence or absence of 1st normal pulp-like tissue, 2nd newly hard tissue (bone,cementum, dentin),3rd empty/necrosis,4th intra-canal inflammation, 5th periapical inflammation, 6th apical narrowing and wall thickening. Results: The results have shown that 85.71% of specimens had normal pulp-like tissue ,100% had newly hard tissue structure, 14.28% had an empty canal necrosis, 57.14%had intra-canal inflammation, 71.42% had periapical inflammation, and 85.71% had apical narrowing. Conclusion: The pulp stem cell homing procedure showed an effective way to treat an open apex tooth and this procedure was increased the root length and thickness and also filled the pulp space with pulp-like tissue. The procedure did not regenerate the tooth structure, but formed a tissue like dental structure (dentin, bone and cementum) and these tissues did not for regeneration, but for tissue repair.